Comparison on self-determination, peer-relationship, and alienation in physical education of early adolescent in Korea and China - Jaeuk, Jeong; Yu, Sun; Donghwi, Suh (Frontiers in Psychology, 2024)
In order to identify effective strategies for enhancing a high-quality physical education system, it is imperative to undertake research that examines the nuances of educational culture, specifically focusing on the psychological experiences of early adolescents within physical education classes. This study aims to compare self-determination, peer-relationships, and feelings of alienation in physical education among adolescents from Korea and China, both situated in East Asia, with respect to their nationality and gender. 122 early adolescent males (M = 14.34, SD = 0.65) and 78 females (M = 14.34, SD = 0.64) from South Korea and 125 early adolescent males (M = 14.13, SD = 0.58) and 70 females (M = 14.13, SD = 0.59) from China participated in this study, with a mean age of 14.24 ± 0.62. The Academic Self-Regulatory Scale (SRQ-A), Peer-relationship Questionnaire, and a Scale for Measuring Student Alienation in Physical Education were utilized for data analysis. For statistic comparisons, a t-test was used. Self-determination of male and female students in China was significantly higher than that of male and female students in Korea respectively. Peer-relationship of male students in Korea was significantly higher than that of male students in China. Physical education alienation of the female students in Korea was significantly higher than that of male students in Korea. Given that the influence of self-determination, peer-relationships, and physical education alienation varies by nationality and gender, it is crucial to seek and implement strategies to develop an effective physical education system. By doing so, physical education alienation can be minimized and prevented, ultimately preserving the health and well-being of adolescents. This approach is vital for fostering a supportive and inclusive environment that promotes lifelong fitness and health.